35 Prevalence of brugada syndrome in high risk irish population – data from cardiac risk in younger persons (CRYP), Tallaght, Dublin. (28th September 2016) - Ranganathan, D; Connaughton, H; Sulaiman, H; Ward, D
Abstract : Introduction: Brugada Syndrome (BrS), first described by 2 Spanish brothers, is a genetic arrhythmogenic disease characterised by appearance of coved-shaped STelevation on electrocardiogram (ECG) in precordial leads V1–V3 in the absence of structural heart disease, electrolyte imbalance or ischemia. It is associated with syncope and sudden death, typically at rest or during sleep. Methods: We used our CRYP database to identify individuals as having probable BrS based on clinical presentation, family history and result of provocation test using ajmaline. Ajmaline, a short-acting sodium channel blocker, unmasks these dynamic, and often concealed, BrS ECG changes. Ajmaline dosed at 1 mg/kg body weight was infused at a rate of 10 mg/min with continuous ECG monitoring, with modified lead placement as per protocol (1). The test was deemed positive with the development of abnormal coved-type ECG changes in precordial leads V1–V3. Results: Of 207 patients (85 families) selected for ajmaline testing, 193 underwent provocation testing. The most common indication for referral was family history of sudden cardiac death (161), followed by symptoms of syncope (11), patients with a known family history of BrS (8), patients who suffered cardiac arrest/non-sustained ventricular tachycardia (5), patients with borderline ECG that did not fit the criteria for BrS (4), patients presenting with palpitations (2) and seizures (2). (Figure 1 ) 10 patients (6 males, 4 females) developed Type 1 ECG changes, 2 developed Type 2 changes and 2 developed QRS prolongation. Of the 10 who were positive, 6 patients belonged to 2 families and 4 were unrelated. 2 patients subsequently underwent ICD placement. The rest of the patients remain well and are routinely followed up for development of symptoms. Conclusion: Sudden arrhythmic death syndrome (SADS) is defined as a sudden, unexpected death in a person with no known prior cardiac disease, last seen well within 12 hours of the death and within 1 hour of the onset of symptoms (if any) in whom a full post-mortem examination including toxicology investigations could not identify the cause of death (2). In Ireland SADS has reported incidence of 0.76 per 100, 000 compared to 0.16 per 100, 000 in the United Kingdom (3). In our study, out of 85 families screened through ajmaline test for BrS, 6 families were found to have evidence of BrS (7%). A similar study by McGorrian et al, in which 73 families were screened for SADS in Ireland, the results were very similar. They identified 22 families with a potential inheritable cause of SADS, of which 5 families were found to have evidence of BrS (7%). These identical results suggest that Brugada syndrome is a relatively rare but definite cause of sudden cardiac death in the Irish population. Ajmaline testing should considered and routinely performed in patients screened for SADS.